Perpetual West : a novel - Maren, Mesha (Algonquin Books of Chapel Hill, 2022)
"As Alex and Elana try to make their home among the academics and young leftists in El Paso and Juárez, they are pulled from each other by an affair with a lucha libre fighter, their struggles to define themselves, and the loud cry of home"--